Marketing of the gambling industry - Rožek, Jan; Štědroň, Bohumír, 1948-; Stříteský, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
This thesis is studying the current global as well as Czech gambling industry with the focus on internet gambling activities. The work begins with the description of various gambling activities. The focus is taken on the internet gambling activities with description of the specifics and the current European as well as US legal frame. Next part is dedicated to the psychology of gambling together with the pathological gambling addiction. In next part the thesis studies the current situation on the Czech market - history, main official legal providers as well as main grey market providers. Second part of the work is the case study of the launch of the internet lottery games by Fortuna Entertainment Group. This case study is based on a desk research of previous successful best practices in the internet gambling industry from all around the world.
Vedoucí práce: Bohumír Štědroň
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses